Influence of the geometry of equal-transect oblique tunnel portal on compression wave and micro-pressure wave generated by high-speed trains entering tunnels. Issue 178 (July 2018) - Zhang, Lei; Thurow, Kerstin; Stoll, Norbert; Liu, Hui
Abstract: Pressure gradient and micro-pressure wave induced by a high-speed train entering a tunnel were investigated for the parametric design of equal-transect oblique tunnel portal. A moving model experimental test was conducted to verify the computational method and mesh. The influence of three main factors (portal shape, slope value, and aperture ratio) of the equal-transect oblique tunnel portal were considered in this study. The results showed that the hat oblique shape was the most efficient portal design to alleviate the pressure gradient and micro-pressure wave compared to the other designs examined in this study, and the mitigation mechanism of the hat oblique design on the initial compression wave was explained. Then the effects of the slope value and the aperture ratio of hat oblique tunnel portal on the pressure gradient and micro-pressure wave were investigated, and the parameters of the equal-transect oblique tunnel portal were optimized to alleviate the pressure gradient and micro-pressure wave induced by high-speed trains entering tunnels. Highlights: Effects of oblique tunnel portal shapes, slope values and aperture ratio of the vented holes were studied. Hat oblique tunnel portal was the most efficient portal. Pressure gradient and micro-pressure wave can be alleviated by reducing the slope value of the hat oblique tunnel portal. The most efficient aperture ratio of the vented holes opened on the hat oblique tunnel portal was 0.14.